Situation Report: Baltic Area, 28 October 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Comment on the Estonian Popular Front / by Vladimir Kusin Latvian-Russian Relations and Latvian Activism / by Dzintra Bungs A Hebrew Cultural Society Founded / by Dzintra Bungs First Secretary Songaila on the Restructuring Movement's Constituent Congress / by Kestutis Girnius Congress of the Lithuanian Restructuring Movement / by Saulius Girnius